Effects of the Applied Potential on the Performance of Polysulfone Membranes Functionalized with Sulfonated Polyether Ether Ketone Polymers - Abelline Fionah; Kate McLarney; Aviana Judd; Isabel C. Escobar (Membranes, 2023)
The global water crisis growth has led to a tremendous increase in membrane technology research. Membranes are favored over many other technologies for water treatment because, in principle, they require no chemical additives and can be used isothermally at low temperatures. Membranes that can reject contaminants and salts, produce adequate permeate flux values, and require minimal cleaning are highly demanded. However, most synthesized membranes on the market have associated problems, such as membrane fouling; inverse relationships between flux and solute rejection; and the high cost of synthesis, operation, and maintenance. Therefore, there is a continuied need to produce membranes with properties that make them able to sustain flux and selectivity over time. This research study focused on increasing the surface charge and hydrophilicity of polysulfone (PSf) membranes by incorporating sulfonate-functionalized poly-ether-ether-ketone (SPEEK) into PSf/N-Methyl-2-pyrrolidone (PSf/NMP) membranes. The sulfonation of the PEEK provided a net increase in negative charge on the surface of the membranes that enabled charge repulsion to take place, thus increasing the rejection of ions. In this project, the effect of the applied potential on the performance of SPEEK: PSf/NMP membranes was evaluated. The characterization of the as-synthesized membranes was carried out using the surface’s structure and morphology, contact angle, and zeta potential. Furthermore, a voltage of 1.5 V was applied to the membranes in the presence of various salts (sodium chloride, calcium chloride, and potassium chloride salts) to evaluate the effects of the applied potential on solute rejection. It was found that both the permeability and the selectivity of the membranes increased when the voltage was applied. The obtained results indicate that incorporating SPEEK into PSf/NMP membranes increased the hydrophilicity of the membranes, and under the applied voltage, the incorporation allowed it to function as an electrodialysis process that is capable of removing ions from water bodies by utilizing the charge repulsion of ions.